2021
DOI: 10.1038/s41467-021-25829-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic essentiality between PTEN and core dependency factor PAX7 dictates rhabdomyosarcoma identity

Abstract: PTEN promoter hypermethylation is nearly universal and PTEN copy number loss occurs in ~25% of fusion-negative rhabdomyosarcoma (FN-RMS). Here we show Pten deletion in a mouse model of FN-RMS results in less differentiated tumors more closely resembling human embryonal RMS. PTEN loss activated the PI3K pathway but did not increase mTOR activity. In wild-type tumors, PTEN was expressed in the nucleus suggesting loss of nuclear PTEN functions could account for these phenotypes. Pten deleted tumors had increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 74 publications
(127 reference statements)
2
8
0
Order By: Relevance
“…Cells were then incubated for 4 h at 37 C. Cells were treated with trametinib (16292, Cayman Chemical, Ann Arbor, MI, USA) or rapamycin (13346, Cayman Chemical) at indicated concentrations or a kill control (20% DMSO) for 72 h. Cell viability was determined using the Cell Titer Glo Assay (G7570, Promega, Madison, WI, USA) measuring luminescence with a BioTek Synergy 2 (BioTek/ Agilent, Winooski, VT, USA). The percentage of growth inhibition was calculated using the following formula: (luminescence of treated wellluminescence from kill control)/(luminescence of vehicle treated wellluminescence from kill control) [28].…”
Section: Cell Lines and Allograftsmentioning
confidence: 99%
“…Cells were then incubated for 4 h at 37 C. Cells were treated with trametinib (16292, Cayman Chemical, Ann Arbor, MI, USA) or rapamycin (13346, Cayman Chemical) at indicated concentrations or a kill control (20% DMSO) for 72 h. Cell viability was determined using the Cell Titer Glo Assay (G7570, Promega, Madison, WI, USA) measuring luminescence with a BioTek Synergy 2 (BioTek/ Agilent, Winooski, VT, USA). The percentage of growth inhibition was calculated using the following formula: (luminescence of treated wellluminescence from kill control)/(luminescence of vehicle treated wellluminescence from kill control) [28].…”
Section: Cell Lines and Allograftsmentioning
confidence: 99%
“…RMS therapy requires a multimodal approach, consisting of surgery, radiotherapy, and chemotherapy (vincristine, dactinomycin, and cyclophosphamide/ifosfamide), resulting in an overall 5-year survival of >70% for localized RMS tumors, while metastatic disease has an unfavorable outcome. Mutations in the PI3K catalytic subunit [ 15 , 16 ], and Fibroblast Growth Factor Receptor 4 (FGFR4) [ 14 , 17 ], and loss of phosphatase and tensin homolog (PTEN) [ 18 ] are found recurrently in RMS to activate the PI3K/Akt/mTOR pathway, which is negatively associated with patient survival [ 19 , 20 , 21 , 22 ]. The Akt through mTOR complex regulates several important processes, including protein synthesis and inhibition of autophagy [ 23 , 24 ], and mechanisms of cell migration, invasion, and metastasis [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are different animal models to study STS [ 3 , 4 , 5 ], which have revealed the implication of key proteins in sarcomagenesis, as in the case of p53 [ 6 ] or the AKT signaling pathway [ 7 , 8 ]. Indeed, most of this experimental observation has been extrapolated to human pathologies, which will certainly have clinical implications in the coming years.…”
Section: Introductionmentioning
confidence: 99%